PEMBELAJARAN BACA TULIS AL-QUR’AN BAGI ANAK: ANALISIS STRATEGI GURU MENGAJI DI KELURAHAN UJUNG PADANG, PADANGSIDIMPUAN - Liana Astuty Siregar; Sawaluddin Siregar (Yayasan Baitul Hikmah al-Zain, 2025)
This research is motivated by the fact that some children still face difficulties in reading the Qur'an properly and correctly, especially in terms of pronunciation and basic understanding of the reading. This demonstrates the importance of the teacher's role in designing appropriate strategies in learning to read and write the Qur'an. The purpose of this study is to describe the strategies implemented by Qur'an teachers in improving Qur'an reading skills in Ujung Padang Village, Padangsidimpuan. The research method used is a qualitative approach with a descriptive type. Data collection techniques were carried out through direct observation, in-depth interviews, and documentation studies. Data were analyzed through the process of data reduction, data presentation, and drawing conclusions, and verified using triangulation techniques to ensure valid and reliable results. The results show that Qur'an teachers apply six main strategies: selecting an individual approach, establishing learning procedures, selecting varied methods and techniques, determining success indicators, instilling the value of appreciation for reading, and establishing etiquette in reading the Qur'an. These strategies have proven effective in developing Qur'an reading skills while shaping children's character and spiritual attitudes.